2020
DOI: 10.1080/10408398.2015.1020918
|View full text |Cite
|
Sign up to set email alerts
|

Statement of removal

Abstract: Bacteriocins are ribosomally-synthesized antimicrobial peptides or proteinaceous compounds produced by bacterial strains. They are generally effective in inhibiting the growth of similar or closely related bacterial strains. A high diversity of various bacteriocins is produced by many lactic acid bacteria (LAB) and is found in numerous fermented and non-fermented foods. Several bacteriocins from LAB extend potential applications in food preservation, thus help foods to be naturally preserved and richer in orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 106 publications
0
7
0
Order By: Relevance
“…Although results obtained from culture media may show that bacteriocins inhibit target organisms, the application of bacteriocins into foods must be tested to confirm their effectiveness. Many studies showed the potential of applying bacteriocins or bacteriocin-producing strains into foods, such as meat, dairy products, fish, alcoholic beverages, salads, and fermented vegetables ( O’Sullivan et al, 2003 ; Ramu et al, 2015 ). To date, only nisin (Nisaplin, Danisco) and pediocin PA1 (Microgard TM , ALTA 2431, Quest) have been commercialized as food preservatives ( Simha et al, 2012 ).…”
Section: Application Of Purified/semi-purified Bacteriocins To Dairy mentioning
confidence: 99%
“…Although results obtained from culture media may show that bacteriocins inhibit target organisms, the application of bacteriocins into foods must be tested to confirm their effectiveness. Many studies showed the potential of applying bacteriocins or bacteriocin-producing strains into foods, such as meat, dairy products, fish, alcoholic beverages, salads, and fermented vegetables ( O’Sullivan et al, 2003 ; Ramu et al, 2015 ). To date, only nisin (Nisaplin, Danisco) and pediocin PA1 (Microgard TM , ALTA 2431, Quest) have been commercialized as food preservatives ( Simha et al, 2012 ).…”
Section: Application Of Purified/semi-purified Bacteriocins To Dairy mentioning
confidence: 99%
“…Most of the studied bacteriocins possess good thermo stability thus able to remain stable during thermal processing cycle of foods, while the others can act at low pH and temperature thus finds application in acid foods and cold-stored products (3). Many bacteriocins have been isolated for use as natural food biopreservative (4, 5). Nisin produced by Lactococcus lactis sub sp.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteriocins, defined as biologically active proteins or peptides, are found in almost every bacterial species. Bacteriocins from lactic acid bacteria (LAB), especially, have drawn special attention due to their potential application as natural food preservatives in the food industry ( Udhayashree et al, 2012 ; Gálvez et al, 2014 ; Ramu et al, 2015 ). At present, according to the classification scheme of Klaenhammer ( Klaenhammer, 1993 ; Rea et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%